Vocabulary acquisition with the help of video games : A quantitative analysis on the effects of gaming on vocabulary acquisition - Pakkala, Toni (My University, 2020)
The aim of this Master’s Thesis is to look at how video games affect vocabulary learning. As such, the thesis will first look at some of the theory on language learning, as well as theory on game-based learning (GBL). The theory will also cover flow and game genre discussions because both have been proven to have an effect on learning (Guan 2013, Jensen 2017), In addition, flow has been shown to occur more easily when playing video games (Cowley et al. 2008), therefore making it an important factor to understand when looking at the possible results of GBL. The present study looked at three different age groups, and their video gaming habits, which made it possible to analyse multiple different facets of possible facilitative effects of video games on the participants. The materials were gathered from 21 6th graders, 23 8th graders and from 20 second year upper secondary school students. The questionnaire they answered gave information on how much they played, how often they played and what types of games they played. The participants also took a shorter version of Paul Nation’s (2007) vocabulary size test, where they tested their knowledge some common and some more uncommon words. Since some participants did not play any video games this allowed the present study to compare gamers and non-gamers. The results showed that playing video games has a positive correlation with vocabulary size test scores, and that the genre of the game also has an effect. Future research should look at the co-occurrence of other hobbies with video gaming, to isolate the effects of game-based learning.
Keywords: Vocabulary acquisition, language learning, video games, game-based learning, flow, incidental language learning, comprehensible input